A 195Pt Nuclear magnetic resonance and molecular dynamics computer simulation study of the solvation of simple platinum (IV) chlorido complex anions in water and water-miscible solvent mixtures - Engelbrecht, Leon de Villiers (2017)
Thesis (PhD)--Stellenbosch University, 2017.